Landasan Teologis Pendidikan Agama Kristen dalam Pembentukan Iman Peserta Didik - Heki Saogo; Seriya Seriya; Sandra Rosiana Tapilaha (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Christian Religious Education (PAK) plays a crucial role in helping students develop faith based on the truth of God's Word. Therefore, a theological foundation plays a crucial role in the implementation of PAK, ensuring that educational activities are not only focused on knowledge transfer but also directed toward holistically shaping character and strengthening students' faith. This article aims to examine the theological foundation of Christian Religious Education in the process of developing students' faith based on Christian teachings. The method used in this study is literature analysis, examining various theological sources, the Bible, and writings related to Christian education. The findings of this study indicate that the theological foundation of PAK stems from God's calling as a true educator, the example of Jesus Christ as the Primary Teacher, and the role of the Holy Spirit in fostering and maintaining faith. Christian Religious Education based on strong theology can help students experience true growth in faith, internalize Christian values, and implement them in their daily lives.